Early Oral Cancer Diagnosis: Secondary Prevention in the Form of Opportunistic Screening or Organized Screening? - Pinto Silva, Joana Filipa (Gazeta Médica, 2021)
Oral cancer is the sixth most common cancer in the world with around 300 000 new cases annually, with a five-year survival rate after diagnosis of 40%.2 In Portugal, there are about 1000 new cases per year and 500 deaths.2 Oral cancer appears more frequently in men (2: 1 ratio male / female) after the fourth decade, although it has been documented worldwide, an increased number of this cancer in younger adults and women. [...]